Deciphering the Link Between Mental Health and Green Space in Shenzhen, China: The Mediating Impact of Residents' Satisfaction - Qiao, Yuhan; Chen, Zini; Chen, Yuqing; Zheng, Tianxiang (Frontiers in Public Health, 2021)
Rapid urbanization and increasing urban density in China threaten residents’ mental health. As a vital component of built environments, green space plays a key role in individuals’ psychological well-being; however, the mediating effect of residents’ satisfaction with the green space environment on the relationship between urban greening and residents’ mental health in Chinese contexts has yet to be thoroughly explored. To fill this knowledge gap, this paper attempts to reveal the internal logic and mechanism underlying the linkages between green space, residents’ mental health, and their satisfaction with green space in Shenzhen, China. Specifically, this paper explores the mediating role of residents’ satisfaction with a green space environment using questionnaire survey data, “Quick Bird-2” high-resolution remote sensing image data, and a multilevel regression model. Our empirical findings indicate that the relative range of neighboring green spaces can directly improve residents’ mental health. More importantly, the relationship between the relative scope of green space and residents’ mental health is mediated by residents’ satisfaction with the green space environment rather than its direct health effects. Given the influence of green space on residents’ satisfaction with the environment, green space indirectly affects mental health. These findings should provide the government useful guidance for considering the spatial distribution and quantity of green space. Our results should also help residents improve their actual experiences and subjective satisfaction with the green space environment.